USING A PORTABLE MULTI!ANGLE SPECTROPHOTOMETER IN THE FORENSIC ANALYSIS OF PAINTS AND COATINGS - G. Bocharov; O. Khatunceva (Теория и практика судебной экспертизы)
In this paper, an algorithm for solving the question of the presence of a defect colordi!erence repair body elements with respect to the factory this issue and the basicinformation about the device BYK-mac COLOR and software-based, which are used in RFCFS. The practice of using the device in question and conducted with the help of his means of examination, and the virtual absence of call experts to testify in court in sug- gestive explaliations on the study showed the e!ectiveness of using a spectrophotometer BYKmac COLOR.